2020
DOI: 10.29312/remexca.v0i24.2353
|View full text |Cite
|
Sign up to set email alerts
|

Rendimiento de trébol blanco asociado con pasto ovillo a diferentes frecuencias de pastoreo

Abstract: El objetivo del estudio fue evaluar el comportamiento del trébol blanco (Trifolium repens L.) asociado con pasto ovillo (Dactylis glomerata L.) a cuatro frecuencias de pastoreo. Los tratamientos fueron las frecuencias fijas de 28 d en primavera-verano y 35 d en otoño-invierno y cuando la pradera intercepto 95 y 100% de radiación interceptada. Los tratamientos se asignaron a unidades experimentales de acuerdo con un diseño de bloques al azar en parcelas divididas con tres repeticiones. Las variables evaluadas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Estas condiciones determinan al pasaje al estado reproductivo de las especies sembradas y las implicancias en una mejor distribución de la luz a estratos inferiores, hojas de mayor elongación y distribución de asimilatos en favor a la parte aérea (Parson 1988). La disminución en la biomasa producida a mayores precipitaciones se explica por una mayor cantidad de días con lluvias y por lo tanto menor cantidad de radiación efectivamente recibida que limita la eficiencia de transformación de luz y en biomasa aérea (Ventura Ríos et al, 2020). La menor producción del lado izquierdo del árbol de clasificación está determinada por una menor radiación incidente y precipitaciones mayores a 400 mm, que son características que indican condiciones desfavorables para la fotosíntesis y liberación de nutrientes por parte de la biomasa microbiana del suelo y por lo tanto limitantes importantes para la fotosíntesis (Nabinger, 1998).…”
Section: Efecto De La Dotación En La Producción De Materia Secaunclassified
“…Estas condiciones determinan al pasaje al estado reproductivo de las especies sembradas y las implicancias en una mejor distribución de la luz a estratos inferiores, hojas de mayor elongación y distribución de asimilatos en favor a la parte aérea (Parson 1988). La disminución en la biomasa producida a mayores precipitaciones se explica por una mayor cantidad de días con lluvias y por lo tanto menor cantidad de radiación efectivamente recibida que limita la eficiencia de transformación de luz y en biomasa aérea (Ventura Ríos et al, 2020). La menor producción del lado izquierdo del árbol de clasificación está determinada por una menor radiación incidente y precipitaciones mayores a 400 mm, que son características que indican condiciones desfavorables para la fotosíntesis y liberación de nutrientes por parte de la biomasa microbiana del suelo y por lo tanto limitantes importantes para la fotosíntesis (Nabinger, 1998).…”
Section: Efecto De La Dotación En La Producción De Materia Secaunclassified
“…Therefore, the PAM are those infrastructures, effluents, emissions, remains or waste deposits produced in the mining operation, which constitute a permanent and potential risk to the health of the population (Gutierrez Torres and Valqui Rojas, 2021). It is important to mention that white clover (Trifolium repens) tends to dominate in associated meadows over time due to its stoloniferous growth habit, obtaining a greater advantage compared to orchard grass (Dactylis glomerata) that are tillered and erect (Ventura Ríos et al, 2020;Ministry of Education and Science, 2007). Likewise, the cultivation of forage pastures has the following advantages; Irrigation is easy and simple to carry out, it allows to moisten the soil evenly, the excess water applied can be quickly drained.…”
Section: Designmentioning
confidence: 99%
“…In this sense, Solís-Oba et al (2020) states that white clover (Trifolium repens) and orchard grass (Dactylis glomerata) have a high germination rate, so it would be advisable to cover uncultivated land. Many investigations show that extreme temperatures, the availability of nutrients and pasture ecosystems are changing, the importance of grasses in cold areas are usually called C3 and in warm areas C4; however, in the face of climate change, its behavior may be variable (Ventura Ríos et al, 2020). When cultivating these forage grasses, the pH and temperature must be taken into account, since these grasses will adapt to different climatic changes.…”
Section: Introductionmentioning
confidence: 99%
“…White clover is characterised by its essential contribution of protein in the diet of animals [16] and by its capacity to fix nitrogen and improve the productivity of this association [23]; however, it has been found that values lower than 20 % of white clover in associated pastures seriously affect these indicators, in addition to restricting the total daily intake of nutrients. The presence of white clover in pastures should not be above 50 % to meet the nutritional requirements of animals and the release of nitrogen to the environment [24,25] For Tilus et al (2022) [11], forage yield increases linearly as the time of cutting is prolonged thus yields have been obtained in this association of 1470 kg DM ha −1 when this is done around 10 cm in height with a remnant greater than 4 cm [6]; 2000 kg DM ha −1 if the height is 13 cm and 2781 kg DM ha −1 if the ryegrass is 29.8 cm [26]; 3974 kg DM ha −1 when the height is 20 cm high and post-grazing remnant of 5 cm [27]. For white clover, heights of 22 cm have been found when cutting every 60 days [28].…”
Section: Of 12mentioning
confidence: 99%